THE IMPACT OF STAR FORMATION AND FEEDBACK RECIPES ON THE STELLAR MASS AND INTERSTELLAR MEDIUM OF HIGH-REDSHIFT GALAXIES - Katz, Harley; Rey, Martin P.; Cadiou, Corentin ; 0000-0003-2285-0332; Kimm, Taysun; Agertz, Oscar (Open Journal of Astrophysics, 2026)
We introduce MEGATRON, a new galaxy formation model for cosmological radiation hydrodynamics simulations of high-redshift galaxies. The model accounts for the non-equilibrium chemistry and heating/cooling processes of ≥ 80 atoms, ions, and molecules, coupled to on-the-fly radiation transfer. We apply the model in a cosmological setting to the formation of a 109 M⊙halo at z = 6, and run 25 realizations at pc-scale resolution, varying numerous parameters associated with our state-of-the-art star formation, stellar feedback, and chemical enrichment models. We show that the overall budget of feedback energy is the key parameter that controls star formation regulation at high redshift, with other numerical parameters (e.g. supernova clustering, star formation conditions) having a more limited impact. As a similar feedback model has been shown to produce realistic z = 0 galaxies, our work demonstrates that calibration at z = 0 does not guarantee strong regulation of star formation at high-redshift. Interestingly, we find that subgrid model variations that have little impact on the final z = 6 stellar mass can lead to substantial changes on the observable properties of high-redshift galaxies. For example, different star formation models based on, e.g. density thresholds or turbulence inspired criteria, lead to fundamentally distinct nebular emission line ratios across the interstellar medium (ISM). These results highlight the ISM as an important resource for constraining models of star formation, feedback, and galaxy formation in the JWST era, where emission line measurements for > 1, 000 high-redshift galaxies are now available. Subject headings: high-redshift galaxies, ISM, galaxy formation.